Mental Health A Conversation with Elyn Saks. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Elyn Saks, Orrin B. Evans Distinguished Professor of Law, and Professor of Law, Psychology and Psychiatry and the Behavioral Sciences at USC. During this wide-ranging conversation Elyn Saks candidly shares her personal experiences with schizophrenia and discusses the intersection of law, mental health and ethics: the legal and ethical implications surrounding mental health. Further topics include psychotropic medication and the law, criminalization and mental illness, and an exploration of which countries are more.